The Self-Regulating Profession - Shaked, Avner; Sutton, John (Review of Economic Studies, 1981)
Slayton and Treblicock (1978)), the formal analysis of the economics of the self-regulating profession has received little attention from theorists. If a profession is self-regulating, in the sense that its current members, being the sole suppliers of a certain type of service, are free to determine, in one way or another, whether or not to admit a potential recruit, then it might seem prima facie that such a profession could simply be regarded as a monopolistic seller of the service in question, so that the effects of self-regulation would appear to involve an unambiguous welfare loss. The whole rationale for self-regulation, however, rests on the notion that it provides a vehicle through which the quality of the service may be maintained in markets where the consumer cannot readily measure this quality himself. It is the analysis of the interplay of these two elements, the enhanced price of such services associated with the monopolistic power of the profession, and the improved quality of the service which may accompany a reduction in supply, which forms the focus of the present paper. It is tempting to begin the analysis of such a profession by first positing some particular